The Influence of Product Price and Quality on Customer Repurchase Intentions Through Customer Satisfaction Mediation - Aprillia Zimbalis; Nofrisel Nofrisel; Mustikasari Mustikasari (Riviera Publishing, 2024)
This research was conducted with the aim of knowing the influence of prices and products on PT. XYZ Forwarding Indonesia on Repurchase Intention with customer satisfaction as an intervening variable. This affects business competition conditions in the Freight Forwarding industry. Currently, many Freight Forwarding companies have just been established and dare to provide the best offers to attract their customers. The type of research used is quantitative research using a questionnaire as a data collection instrument. The population in this study was PT service users. XYZ Forwarding Indonesia, the sample used was 154 people who had used the service at least twice. The sampling technique used is Probability Sampling. Data analysis technique through SEM-PLS measurements with the help of Smart PLS 4.0.5.9. Software. Based on the results of SEM analysis, the results show that price has a positive effect on customer satisfaction. On the other hand, price has a negative effect on repurchase intention. Then the product is stated to have a positive effect on customer satisfaction and the product also has a positive effect on repurchase interest. Customer satisfaction has a positive effect on repurchase interest. Furthermore, products do not have a direct influence on repurchase interest but are mediated through customer satisfaction. Price also does not have a direct influence on repurchase interest and is mediated through customer satisfaction. So from a Freight Forwarding perspective, companies must pay attention to price in each sale to be able to fulfill customers' desires and make repeat purchases.